Agmatine protects against MAFLD via decreasing RBM15/IGF2BP2-mediated m6A modification of SREBP1 - Guangkui Bu; Yu Li; Guangfu Lin; Lichun Han; Deyi Chen; Xiaoping Lv (Molecular Biology Reports, 2026)

HP-β-CD-functionalized hydrogel SERS fingerprinting for rapid storage-year discrimination of white tea - Zhenglong Chen; Zhile Zhao; Yuxin Bu; Xinyan Yang; Yulin Fang; Hui Lin; Yudong Lu (Food Research International, 2026)

pH-Controlled co-adsorption and selective separation for Cs+ and Sr2+ by an ultra-stable layered titanoniobate - Zhi-Hua Chen; Hao-Wei Lin; Bu-Bu Gao; Hai-Yan Sun; Tian-Yu Pan; Mei-Ling Feng; Xiao-Ying Huang (Chemical Engineering Journal, 2026)

Mechanism-anchored ecological risk assessment of phthalates in coastal waters: Bridging environmental fate and molecular toxicity via an AOP framework - Shao-Yang Bu; Li-Ju Tan; Yan-Shan Chen; Kun Lin; Jiang-Tao Wang (Marine Pollution Bulletin, 2026)

Eccentric compressive performance of CFST columns reinforced with annular stiffeners - Ke-Rong Luo; Bing-Lin Lai; Liang Yu; Bu-Hui Li; Gan-Ping Shu (Engineering Structures, 2026)

Experimental study and numerical simulation on a multi-stage counter-current continuous fluidized bed reactor for activating iron-based Fischer-Tropsch synthesis catalyst - Zhanqi Yang; Chengxiang Li; Yifeng Bu; Tao Wang; Ruili Tong; Hairui Lin; Yongmin Zhang; Zhuowu Men; Youwei Cheng (Chemical Engineering Journal, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Enhanced daily retrieval of Evapotranspiration from a Transformer-based deep learning model combined with satellite passive microwave and optical observations - Fei Bu; Qingyang Liu; Peng Zhang; Lin Chen; Jiheng Hu; Haoyang Li; Yipu Wang; Rui Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Global climate change reshapes nanoparticles' fate: rethinking risks and opportunities for soil-plant health - Xinyuan Bu; Shiyan Qiao; Danxing Yang; Xinyu Wang; Xin Liu; Luo Lin; Yuan Yang; Ali A. El-Keblawy; Kareem A. Mosa; Yaoyu Zhou (Environmental Research, 2026)

Study on the synergistic high-temperature corrosion mechanism of NH3-H2S on different water wall tube materials under a strongly reducing atmosphere in an ammonia-coal co-firing environment - Rui Ma; Guoqiang Bu; Tiantian An; Bo Wei; Qianjin Lin; Lijuan Chen; Shan Wang; Kunpeng Liu; Lijie Song (Fuel, 2026)

Beyond Borders: Tracking Water and Carbon Footprints of Global Transport Modes - Chenglong Wang; Xuewei Guo; Chenyang Shuai; Xi Chen; Wei Huang; Lin Gan; Jingran Sun; Bu Zhao (Water Resources Management, 2026)

Synergistic enhancement of polyvinyl alcohol coating via montmorillonite reinforcement and chemical cross-linking for high-barrier food packaging - Qingmei Zhu; Jiji Fan; Yanan Bu; Xiuqiong Chen; Huiqiong Yan; Qiang Lin (Applied Clay Science, 2026)

Genetic regulation of insulin resistance surrogate index (TyG) and susceptibility to common diseases based on phenome-wide association study - Jia-Xin Wu; Ling-Huan Bu; Pei He; Ming-Hui Xia; Lin Bo; Fei-Yan Deng; Shu-Feng Lei (Molecular and Cellular Biochemistry, 2026)

Reconstructing the Seawater Temperature Field of the Yellow Sea Using TCN-U-Net++ - Jiapeng Bu; Zi Guo; Junqi Cui; Shuyi Zhou; Lei Lin; Shaolei Lu; Xiaodong Liu; Xiaoqian Gao (Journal of Marine Science and Engineering, 2026)
The Yellow Sea is an important offshore area in China, and the accurate prediction of its seawater temperature is of great significance for marine environmental monitoring and climate adaptation management. However, existing research on predicting the three-dimensional (3D) temperature field in the Yellow Sea is scarce and insufficiently accurate. This study proposes a TCN-U-Net++ fusion model to reconstruct the Yellow Sea temperature field using remote sensing satellite data and SODA reanalysis data, while considering the influence of a series of factors, including wind (USSW and VSSW), absolute bathymetric data (BAT), sea surface height anomaly (SSHA), latitude (LAT), longitude (LON), solar radiation (SR), surface runoff (SRO), and precipitation (P). The results show that the model can accurately capture the temporal and spatial distribution characteristics of the temperature field in the Yellow Sea. The results indicate that the deviations from SODA are generally within 2 °C, with errors being approximately 45% lower than those of other models, while the prediction errors relative to Argo and voyage observations are mostly within 1 °C, further demonstrating the accuracy and robustness of the proposed model. In addition, the predictions of the Yellow Sea Cold Water Mass (CWM) are highly consistent with SODA in terms of their evolution and key characteristic parameters. Specifically, the maximum deviation in core temperature is only 0.3 °C, and the difference in its spatial extent is less than 1%. The results demonstrate that TCN-U-Net++ effectively enhances the accuracy of 3D sea temperature prediction in the Yellow Sea, providing technical support for temperature monitoring, ecological early warning, and climate change research.

Physicochemical, microstructural, and Vis/NIR optical properties of kiwifruit during bruise-induced ripening - Youhua Bu; Shuai Li; Mingzhuang Lin; Chengxu Gong; Rui Wang; Wenchuan Guo (Postharvest Biology and Technology, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Peimisine-sulfide improves inflammation caused by copper sulfate through inhibiting ferroptosis using zebrafish embryos - Siyu Chen; Junyu Liang; Tingting Lin; Zitong Huang; Leyan Huang; Liang Bu; Chuanzhi Kang; Chengyong He (Journal of Environmental Sciences, 2026)

Synergistic RuPt alloy nanoparticles on halloysite nanotubes for efficient decarboxylation of stearic acid to green diesel under mild conditions - Jiaxin Zhou; Zitao Lin; Peng Yuan; Hongling Bu; Meiqing Chen; Honghai Wu; Yanfu Wei (Chemical Engineering Journal, 2026)

Parametric calibration in bonded block models for simulating mechanical behaviours of intact rocks using machine learning - Fengchang Bu; Ruoshen Lin; Michel Jaboyedoff; Wei Liu; Lei Xue (International Journal of Rock Mechanics and Mining Sciences, 2026)

Light-responsive biopolymeric films embedded with natural polyphenols: ROS-mediated suppression of postharvest microbial decay in perishable fruits - Xianrui Chen; Lin Wang; Lihong Lin; Nitong Bu; Di Zhang; Zhenzhen Wu; Wei Liu; Jie Pang (Food Control, 2026)

Disruption of sphingolipid metabolism triggers lung vascular inflammation and aging-like changes under hypoxia through VDAC1-mediated mitochondrial DNA release - Jin Xu; YiLing Ge; Bin Zhang; SiYuan He; QingLin Cao; PeiJie Li; YingRui Bu; YunGang Bai; Lin Zhang; GuoDong Tan; Jin Ma; ManJiang Xie (Apoptosis, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Phytochemicals and health-promoting evaluations of Ophiorrhiza puffii , a chinese endemic plant - Qing Bu; Qi-Bin Yang; Zeng-Yue Ge; Ze-Xiong Shi; Lin-Fu Liang (Natural Product Research, 2026)

Stable soil aggregates and complex microbial networks enhances soil quality in saline-alkali agroecosystem - Bangyan Zhang; Jinmin Wu; Rui Bu; Xiaoli Zhang; Xiaolong Bai; Lei Li; Meilin Lin; Yifei Zhang; Xing Xu; Bin Wang (Plant and Soil, 2026)

Unveiling the submerged iceberg of semi-volatile organic pollutants in surface water across the Yangtze River Basin - Quanzhen Liu; Xiong Xu; Mengru Yang; Qingwei Bu; Yongchang Xie; Lihua Lin; Lu Bai; Donghong Wang (Water Research, 2026)

Development of a visual rapid detection method for aquatic animal-derived Trypanosoma via MIRA-LFD - Xue-Mei Yuan; Xin-Zhi Weng; Xia-Lian Bu; Jing Chen; Jing-Biao Jiao; Xian-Qi Peng; Wei-Song Ma; Ling-Yun Lin; Lei Huang; Xiao-Yi Pan; Hong-Xia Hu; Ling-Wei Xu; et al. (Veterinary Parasitology, 2026)

Initial size distribution of cough particles for CFD simulations based on particle sizer measurements and evaporation model - Yunchen Bu; Hideki Kikumoto; Wonseok Oh; Chao Lin; Ryozo Ooka (Journal of Aerosol Science, 2026)

Electrochemical synthesis of H2O2 integrates reaction mechanisms, reaction media, mass-transfer effects, and device design - Lin Zhu; Rong Ma; Yixin Bai; Feng Li; Gao-feng Han; Yunfei Bu (Chemical Engineering Journal, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Innovative cellulose-based porous matrix loaded with carvacrol microemulsion for sustainable mango preservation - Linyun Mou; Jianlong Li; Ya Lu; Lin Wu; Guijun Bu; Juan Li; Ganpeng Li (International Journal of Food Microbiology, 2025)

A revisiting of 2021 Japanese electricity spot market dysfunction event: How it happened and what can we learn from it? - Hong-Zhou Li; Lin-Lan Bu; Maria Kopsakangas-Savolainen; Mika Goto (Energy Policy, 2025)

Quaternary-ammonium chitosan/Sericin-modified carbon nanotubes Photothermal coatings: A reusable and sustainable chemical-free seed disinfection strategy - Xianrui Chen; Lin Wang; Lihong Lin; Chen Ma; Zhenzhen Wu; Nitong Bu; Di Zhang; Wei Liu; Jie Pang; To Ngai (Carbohydrate Polymers, 2025)

Polyacrylonitrile (PAN) electrospun nanofibrous membrane for removing indoor gaseous phthalates: A health-driven framework for macro-channel adsorption module design and its implications - Yu Sun; Donghui Mo; Lvyan Lin; Hongyi Wang; Jianping Cao; Zhongming Bu (Journal of Hazardous Materials, 2025)

Bioremediation of diesel-contaminated seawater by a novel yeast Candida sp. AC06 capable of synchronously degrading hydrocarbon and producing biosurfactant: Performance and genomic mechanism - Ning Zhang; Xiaoyun Lin; Zhongyong Yan; Chunlei Chen; Yajun Li; Xuming Yang; Xing Ren; Xuefeng Wei; Chunfang Zhang; Kuiyong Bu; Hanghai Zhou (Journal of Environmental Chemical Engineering, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

CO2 adsorption and separation properties of decorative paper impregnated with amino-functionalized cellulose nanofibers/waterborne acrylic resin - Xiaopin Bu; Qian Wei; Zhuoxin Liao; Yuding Zhu; Meiling Chen; Junhui Yang; Xiuzhen Lin; Donggyun Kim; Xiangyu Wang; Song Li; Jeonghun Kim; Wenkai Zhu (Chemical Engineering Journal, 2025)

Fabrication of nonionic surfactant modified montmorillonite for alginate/organo-montmorillonite composite fibers based hydrophobic pharmaceutical formulations - Yanan Bu; Xiuqiong Chen; Ting Wu; Jiji Fan; Haizhen Dai; Huiqiong Yan; Qiang Lin (Applied Clay Science, 2025)

Chemotaxonomically significant phytochemicals with α-glucosidase and tyrosinase inhibitory activities from Chinese endemic plant Ophiorrhiza hunanica - Qing Bu; Qi-Bin Yang; Can-Qi Liu; Zeng-Yue Ge; Xiao-Wen Liao; Lei Wu; Lin-Fu Liang (Natural Product Research, 2025)

Occurrence and ecological risks of pharmaceuticals along the Yangtze River Basin of China: Insights from target analysis and suspect screening strategy - Chong Chen; Chengcheng Bu; Qi Wang; Yutong Zhang; Shaopeng Xu; Yu Hua; Ruolan Jia; Huiju Lin; Xiaolei Wang; Zhiwei Gan; Xiong Xiong; Limin Ma; et al. (Journal of Hazardous Materials, 2025)

Synergistic 3D nanofibers for enhanced microbial control and moisture regulation in fruit preservation - Lin Wang; Wei Liu; Xianrui Chen; Zhenzhen Wu; Nitong Bu; Huimin Xiao; Chen Ma; Jingcheng Hao (Chemical Engineering Journal, 2025)

Advanced materials for combined photodynamic and immunotherapy: Mechanisms and translational opportunities - Suizhi Zou; Kehua Hu; Xiaowan Guo; Lin-Lin Bu; Hui Qiu; Qiuji Wu (Chemical Engineering Journal, 2025)

Karst Trough Control of Solute Transport Processes at Two Karst Groundwater Flow Systems, Western Hubei, Central China - Yi’an Wang; Ruichao Zhao; Lin Ding; Shuai Xiong; Yin Li; Jianwei Bu; Wei Chen; Hong Zhou; Wei Liu (Journal of Earth Science, 2025)

Konjac glucomannan/xanthan gum film embedding soy protein isolate–tannic acid–iron complexes for blueberry preservation - Zhenzhen Wu; Lin Wang; Chen Ma; Mingming Xu; Xiuqing Guan; Fen Lin; Tengjun Jiang; Xianrui Chen; Nitong Bu; Jie Duan; Wei Liu; Jie Pang (Food Hydrocolloids, 2025)

Analysis of main parameters controlling rock avalanche propagation based on machine learning - Ruoshen Lin; Michel Jaboyedoff; Alexander Strom; Marc-Henri Derron; Fengchang Bu (Engineering Geology, 2025)

Histone lactylation-augmented IRF4 is implicated in arsenite-induced liver fibrosis via modulating Th17 cell differentiation - Weiyong Chen; Peiwen Wang; Yan Xie; Daxiao Xie; Hailan Wang; Ning Bu; Jiaheng Lin; Meng Wu; Haibo Xia; Cheng Cheng; Yuanzhong Zhou; Qizhan Liu (Chemico-Biological Interactions, 2025)

Distribution of phthalic acid esters in propolis ethanolic extract and capsuled propolis - Rifat Nowshin Raka; Haitao Xu; Meichao Bu; Lin Zhang; Xiaofeng Xue (Food Additives & Contaminants: Part A, 2025)

Two-photon polymerization 3D printing of biomimetic microstructures for functionalizing surfaces to inhibit bacterial growth - Wentao Zhu; Fang-Yi Huo; Lei-Ming Cao; Zi-Zhan Li; Qian Zhu; Rongxiang He; Bolei Chen; Yong Liang; Bo Cai; Hong He; Lin-Lin Bu; Ligang Hu (Chemical Engineering Journal, 2025)

The combination of metagenomics and metabolomics reveals the effect of nitrogen fertilizer application driving the remobilization of immobilization remediation cadmium and rhizosphere microbial succession in rice - Huan-Zhan Zhou; Bu-Qing Wang; Yong-Hong Ma; Yu-Ying Sun; Huan-Lin Zhou; Zhen Song; Yuan Zhao; Wei Chen; Jie Min; Jing-Wen Li; Tao He (Journal of Hazardous Materials, 2025)

Experimental assessment of rigid surface collision effects on suspended ice particles - Zonghui Liu; Xueqin Bu; Guiping Lin; Ping Huang; Yuli Chen; Dongsheng Wen (Cold Regions Science and Technology, 2025)

Water-in-water emulsions stabilized by konjac glucomannan/tragacanth gum hydrogels for riboflavin delivery - Nitong Bu; Huanglong Lin; Di Zhang; Xianrui Chen; Pingping Tan; Yuanbo Zhong; Liying Huang; Jie Pang; Lin Wang; Ruojun Mu (Journal of Food Engineering, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Enzymatic Stoichiometry and Vector Characteristics Can Indicate Microbial Resource Limitation: Empirical Evidence from Experiment with Multiple Nutrient Addition - Zhifeng Zhai; Liying Lin; Tong Li; Zhaojun Bu; Meng Wang (Ecosystems, 2025)

Emerging role of adaptive immunity in diabetes-induced cognitive impairment: from the periphery to the brain - Genhui Yang; Runtao Su; Jie Bu; Ying Li; Xueling Lin; Jiahui Jin; Yanjun Zhang; Pengwei Zhuang; Hong Guo; Qingsheng Yin (Metabolic Brain Disease, 2025)

The independent and combined associations of nocturnal sleep duration, sleep midpoint, and sleep onset latency with global cognitive function in older Chinese adults - Xueyao Wu; Jiaqiang Liao; Xin Chen; Jinyu Xiao; Xinyang Dui; Tianpei Ma; Lin Hu; Xunying Zhao; Qian Bu; Mengyu Fan; Tao Zhang; Lu Long; et al. (GeroScience, 2025)

A flame-retardant and weakly solvated gel electrolyte for high-performance and high-safety Ah class sodium-ion batteries - Lixing Xue; Hongyan Pan; Yuejun Wang; Zhengyi Wang; Xuhui Wang; Qian Lin; Kuo Zhang; Xiangnan Bu; Maohui Bai; Bo Hong (Chemical Engineering Journal, 2025)

GWAS analysis revealed genomic loci and candidate genes associated with the 100-seed weight in high-latitude-adapted soybean germplasm - Javaid Akhter Bhat; Hui Yu; Lin Weng; Yilin Yuan; Peipei Zhang; Jiantian Leng; Jingjing He; Beifang Zhao; Moran Bu; Songquan Wu; Deyue Yu; Xianzhong Feng (Theoretical and Applied Genetics, 2025)

Inhibitory mechanism of apigenin, quercetin, and phloretin on α-glucosidase - Xin Ren; Xuan Liu; Bu zhen Wang; Min Zhang; Lin xuan Wang (Food Bioscience, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

Estimating Mechanical Parameters of Hydrate-Bearing Sediments on Basis of Shear Wave Velocity Under Triaxial Compression - Lin Dong; Hualin Liao; Yanlong Li; Yajuan Zhang; Qingtao Bu; Gaowei Hu; Nengyou Wu (Journal of Ocean University of China, 2024)

Imaged capillary isoelectric focusing method development for charge variants of high DAR ADCs - Chuan Leng; Shuwen Sun; Wei Lin; Jorge Alexander Pavon; Lynn Gennaro; Rico C. Gunawan; Xiaodong Bu; Tong Yang; Senwu Li (Analytica Chimica Acta, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Phosphorus limitation intensifies heat-stress effects on the potential mutualistic capacity in the coral-derived Symbiodinium - Jiashun Li; Wenzhe Li; Yulin Huang; Hailu Bu; Kaidian Zhang; Senjie Lin (Science of The Total Environment, 2024)

Investigation of verapamil-induced cardiorenal dysfunction and compensatory ion regulation in zebrafish embryos - Jiun-Lin Horng; Bu-Yuan Hsiao; Wen-Ting Lin; Tzu-Ting Lin; Ching-Yen Chang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

TNF-α and RPLP0 drive the apoptosis of endothelial cells and increase susceptibility to high-altitude pulmonary edema - Yi-Ling Ge; Pei-Jie Li; Ying-Rui Bu; Bin Zhang; Jin Xu; Si-Yuan He; Qing-Lin Cao; Yun-Gang Bai; Jin Ma; Lin Zhang; Jie Zhou; Man-Jiang Xie (Apoptosis, 2024)
High-altitude pulmonary edema (HAPE) is a fatal threat for sojourners who ascend rapidly without sufficient acclimatization. Acclimatized sojourners and adapted natives are both insensitive to HAPE but have different physiological traits and molecular bases. In this study, based on GSE52209, the gene expression profiles of HAPE patients were compared with those of acclimatized sojourners and adapted natives, with the common and divergent differentially expressed genes (DEGs) and their hub genes identified, respectively. Bioinformatic methodologies for functional enrichment analysis, immune infiltration, diagnostic model construction, competing endogenous RNA (ceRNA) analysis and drug prediction were performed to detect potential biological functions and molecular mechanisms. Next, an array of in vivo experiments in a HAPE rat model and in vitro experiments in HUVECs were conducted to verify the results of the bioinformatic analysis. The enriched pathways of DEGs and immune landscapes for HAPE were significantly different between sojourners and natives, and the common DEGs were enriched mainly in the pathways of development and immunity. Nomograms revealed that the upregulation of TNF-α and downregulation of RPLP0 exhibited high diagnostic efficiency for HAPE in both sojourners and natives, which was further validated in the HAPE rat model. The addition of TNF-α and RPLP0 knockdown activated apoptosis signaling in endothelial cells (ECs) and enhanced endothelial permeability. In conclusion, TNF-α and RPLP0 are shared biomarkers and molecular bases for HAPE susceptibility during the acclimatization/adaptation/maladaptation processes in sojourners and natives, inspiring new ideas for predicting and treating HAPE.

The aroma profiles of dried gonggans: Characterization of volatile compounds in oven-dried and freeze-dried gonggan - Dongjie Liu; Qiaomei Shen; Kewei Lin; Feng Wang; Zhibin Bu; Jian Peng; Charles Brennan; Soottawat Benjakul; Gengsheng Xiao; Lukai Ma (Food Research International, 2024)

Hepatitis B virus core protein as a Rab-GAP suppressor driving liver disease progression - Yu Su; Fan Bu; Yuanfei Zhu; Le Yang; Qiong Wu; Yuan Zheng; Jianjin Zhao; Lin Yu; Nan Jiang; Yongxiang Wang; Jian Wu; Youhua Xie; et al. (Science Bulletin, 2024)

Intrinsically stretchable tribotronic mechanoplastic artificial synapse - Jianhua Zeng; Libo Chen; Tianzhao Bu; Ziyue Wang; Likun Gong; Zhi-Bin Zhang; Junqing Zhao; Zhong Lin Wang; Chi Zhang (Chemical Engineering Journal, 2024)

All-natural and triple-inspired Janus electrospun fibers with integrated functions for high-performance liquid food packaging - Zhenzhen Wu; Lin Wang; Nitong Bu; Xianrui Chen; Jie Duan; Youxiang Wu; Chen Ma; Jie Pang (Chemical Engineering Journal, 2024)

Has benchmarking improved the performance of the Australian electricity distribution utilities? A meta-frontier model - Lin-Lan Bu; Maria Kopsakangas-Savolainen; Bai-Chen Xie; Hong-Zhou Li; Yi-Meng Liu; Shao-Peng Yin (Utilities Policy, 2024)

Formation behavior of PCDD/Fs during waste pyrolysis and incineration: Effect of temperature, calcium oxide addition, and redox atmosphere - Yuanjun Tang; Dongsheng Tao; Guoneng Li; Chao Ye; Zhongming Bu; Rong Shen; Yonghui Lin; Wei Lv (Environmental Pollution, 2024)

Size dependent photogeneration charge carrier density of hollow ZnIn2S4 microspheres for enhanced photocatalytic activity - Pengfei Zhang; Jie Zhao; Chenyu Lu; Liang Huang; Jianfeng Lin; Zhaoyong Lin; Donglei Bu; Shaoming Huang (Chemical Engineering Journal, 2024)

Intelligent response organo-montmorillonite/Fe3+-alginate/poly (N-isopropylacrylamide) interpenetrating network composite hydrogels for controlled release of water-insoluble pesticides - Hongcai Wang; Xiuqiong Chen; Cuiyu Gong; Yanan Bu; Ting Wu; Huiqiong Yan; Qiang Lin (Applied Clay Science, 2024)

Assessing cardiovascular toxicity in zebrafish embryos exposed to copper nanoparticles - Bu-Yuan Hsiao; Jiun-Lin Horng; Ching-Hua Yu; Wen-Ting Lin; Yu-Han Wang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Permeability enhancement and coal fines removal through oxidation treatment in coalbed methane reservoirs - Yu Lu; Yili Kang; Chengzhong Bu; Ying Li; Chong Lin; Zhenjiang You (Fuel, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

New Steps to Deep-Water Hydrate Long-Term Mining by Formation Stabilization - Dong Lin; Yuhuan Bu; Changyou Xiang; Chang Lu; Huajie Liu; Shenglai Guo (Journal of Marine Science and Engineering, 2023)
The decomposition of hydrates can cause serious sand production and collapse problems, hindering the long-term effective production of hydrates. This study proposes a theory for framework reconstruction and reinforcement for deep-water hydrate layers based on grouting fracturing technology and chemical sand control principles. The setting liquid was injected via fracturing and grouting to form several cracks with a certain depth and width. The setting liquid remains in the fracture and solidifies to form a “reconstruction body.” Simultaneously, the setting liquid permeates and diffuses from the cracks to the surrounding hydrate layer, bonding with the sediment and forming a gradient solidification zone to achieve solidification and reinforcement of the hydrate layer. To achieve effective production of hydrates, the reconstruction body must consider internal reinforcement, sand control, and good permeability. The parameters of the reconstruction body were designed based on the geological characteristics of hydrate formation in a certain area. In order to effectively support the hydrate layer, the reconstruction body was designed with a 24 h compressive strength of at least 3.20 MPa and a long-term compressive strength of at least 17.70 MPa. To ensure that the permeability characteristics of the reconstructed body meet production needs, the permeability of the reconstructed body must be greater than that of the hydrate layer. The maximum concentrated pore size of the skeleton reconstruction body is designed to be 9 μm based on the particle characteristics of shale sand in hydrate reservoirs. This study provides a new approach to solving sand production and collapse.

Removal of Microcystis aeruginosa by manganese activated sodium percarbonate: Performance and role of the in-situ formed MnO2 - Nan Li; Fan Chen; Shunkai Xu; Shumin Zhu; Lingjun Bu; Lin Deng; Zhou Shi; Shiqing Zhou (Chemosphere, 2023)

Enhanced treatment of sludge drying condensate by A/O-MBR process: Microbial activity and community structure - Yin Zhang; Weijie Hu; Lifeng Lin; Shiying Bu; Zhangqin Guan; Jie Zhang; Qiaoying Wang (Chemosphere, 2023)

Improved viability of probiotics encapsulated by layer-by-layer assembly using zein nanoparticles and pectin - Bu Liu; Jielun Hu; Haodong Yao; Lin Zhang; Huan Liu (Food Hydrocolloids, 2023)

PXLink: A simulation program of polymer crosslinking to study of polyamide membrane - Chi Zhang; Guangle Bu; Md Symon Jahan Sajib; Lida Meng; Shiying Xu; Size Zheng; Lin Zhang; Tao Wei (Computer Physics Communications, 2023)

Dl-3-n-butylphthalide activates Nrf2, inhibits ferritinophagy, and protects MES23.5 dopaminergic neurons from ferroptosis - Ziying Ye; Chuna Li; Shuqiong Liu; Hongbin Liang; Jialiang Feng; Danyu Lin; Ying Chen; Sudan Peng; Lulu Bu; Enxiang Tao; Xiuna Jing; Yanran Liang (Chemico-Biological Interactions, 2023)

Predictive models for the aqueous phase reactivity of inorganic radicals with organic micropollutants - Pin Wang; Lingjun Bu; Shiqing Zhou; Yangtao Wu; Lin Deng; Zhou Shi (Chemosphere, 2023)

Comprehensive analysis of lncRNA-mRNA regulatory network in Populus associated with xylem development - Na Sun; Yufen Bu; Xinyuan Wu; Xiaocen Ma; Haobo Yang; Liang Du; Xiaojuan Li; Jianwei Xiao; Jinxing Lin; Yanping Jing (Journal of Plant Physiology, 2023)

GS6.1 controls kernel size and plant architecture in rice - Hongyuan Zhao; Yu Fu; Guiquan Zhang; Yingqin Luo; Weifeng Yang; Xiaoya Liang; Lin Yin; Zhenwu Zheng; Yijun Wang; Zhan Li; Haitao Zhu; Jinyan Huang; et al. (Planta, 2023)

Molecular insights towards changing behaviors of organic matter in a full-scale water treatment plant using FTICR-MS - Shunkai Xu; Yangtao Wu; Lingjun Bu; Lin Deng; Guangchao Li; Shiqing Zhou; Zhou Shi (Chemosphere, 2023)

Assessing the impact of economic growth target constraints on environmental pollution: Does environmental decentralization matter? - Siyu Ren; Mingyue Du; Wenchao Bu; Tao Lin (Journal of Environmental Management, 2023)

Bifunctional lithiophilic carbon fibers with hierarchical structure for high-energy lithium metal batteries - Taiyu Lyu; Fenqiang Luo; Zhen Wang; Futing Jiang; Shize Geng; Yan Zhuang; Xin Lin; Junkai Chen; Dechao Wang; Lingzheng Bu; Lei Tao; Lizhe Liang; et al. (Chemical Engineering Journal, 2023)

PPARγ Regulates Macrophage Polarization by Inhibiting the JAK/STAT Pathway and Attenuates Myocardial Ischemia/Reperfusion Injury In Vivo - Shengnan Wang; Yinlian Cai; Rongsheng Bu; Yaoguo Wang; Qingfan Lin; Youfang Chen; Chunchun Wu (Cell Biochemistry and Biophysics, 2023)

Regulatory role of myo-inositol in the ovarian development of female Chinese mitten crab (Eriocheir sinensis) - Xianyong Bu; Qincheng Huang; Ying Song; Changle Qi; Zhideng Lin; Xiaodan Wang; Meiling Zhang; Chuanjie Qin; Jian G. Qin; Liqiao Chen (Aquaculture, 2023)

Activated AMPK-mediated glucose uptake and mitochondrial dysfunction is critically involved in the glutamate-induced oxidative injury in HT22 cell - Shao-Peng Lin; Jingyi Bu; Shan Ye; Qiangda Xie; Jue-Xian Wei; Xiaofang Yin; Fen Mei; Pei-Yi Lin; Xiao-Hui Chen (Tissue and Cell, 2023)

Health effects of exposure to indoor formaldehyde in civil buildings: A systematic review and meta-analysis on the literature in the past 40 years - Ningrui Liu; Lin Fang; Wei Liu; Haidong Kan; Zhuohui Zhao; Furong Deng; Chen Huang; Bin Zhao; Xiangang Zeng; Yuexia Sun; Hua Qian; Jinhan Mo; et al. (Building and Environment, 2023)

Associations of per- and polyfluoroalkyl substances and their alternatives with bone mineral density levels and osteoporosis prevalence: A community-based population study in Guangzhou, Southern China - Shujun Fan; Yan Wu; Michael S. Bloom; Jiayun Lv; Li Chen; Weiping Wang; Zhi Li; Qinqin Jiang; Li Bu; Jie Shi; Tongxing Shi; Xiaowen Zeng; et al. (Science of The Total Environment, 2023)

Vertical characteristics and potential sources of aerosols over northeast China using ground-based MAX-DOAS - Changyuan Gao; Chengzhi Xing; Wei Tan; Hua Lin; Naishun Bu; Jiexiao Xue; Feng Liu; Wenqing Liu (Atmospheric Pollution Research, 2023)

Transfer organic chloramines to monochloramine using two-step chlorination: A method to inhibit N-DBPs formation in algae-containing water treatment - Da Sheng; Lingjun Bu; Shumin Zhu; Lin Deng; Zhou Shi; Shiqing Zhou (Journal of Hazardous Materials, 2023)

Cu0 incorporated cobalt/nitrogen doped carbonaceous frameworks derived from ZIF-67 (Cu@Co N C) as PMS activator for efficient degradation of naproxen: Direct electron transfer and 1O2 dominated nonradical mechanisms - Jin Zhang; Hanxuan Zeng; Lingjun Bu; Shiqing Zhou; Zhou Shi; Lin Deng (Chemical Engineering Journal, 2023)

Stable isotopes of water as a tracer for revealing spatial and temporal characteristics of groundwater recharge surrounding Qinghai Lake, China - Dong-sheng Li; Bu-li Cui; Yun-duo Zhao; Feng-lin Zuo (Journal of Mountain Science, 2022)

Combining Multiple Factors to Predict Alzheimer’s Disease - Xiao-Lin Gao; Jun Wang; Yan-Jiang Wang; Xian-Le Bu (Neuroscience Bulletin, 2022)

Sex differences in microstructural alterations in the corpus callosum tracts in drug-naïve children with ADHD - Qingxia Lin; Xuan Bu; Hong Chen; Yan Liang; Weiqian Wang; Yanhong Yi; Haixi Lin; Lu Lu; Yingxue Gao; Andan Qian; Shuangli Chen; Meihao Wang; et al. (Brain Imaging and Behavior, 2022)

A microscopic and quantitative analysis on the separation of chloride ion by fly ash washing: Effect of liquid-to-solid ratio, washing time and temperature - Haogang Huang; Wei Liu; Lin Zhang; Jiamei Fang; Fang Xu; Shi Bu; Weigang Xu; Chen Xu; Hongqi Yao; Zhilei Ma (Environmental Science and Pollution Research, 2022)

Epidemiological characteristics of gonorrhea and its influential meteorological factors: a 14-year retrospective assessment in China - Jin Bu; Liang-Jia Zhou; Xiang Xiao; Qian Yue; Gang Hu; Pei Jiang; Jing Chen; Yu Lin (Environmental Science and Pollution Research, 2022)

A performance-oriented adaptability assessment method for TBM tunneling - Chunjin Lin; Zehua Bu; Dongdong Pan; Xiaote Wang; Peng Lin; Yichi Zhang (Arabian Journal of Geosciences, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Mitogenomes provide new insights into the evolutionary history of Prodiamesinae (Diptera: Chironomidae) - Xiao‐Long Lin; Yan‐Min Zhao; Li‐Ping Yan; Wen‐Bin Liu; Wen‐Jun Bu; Xin‐Hua Wang; Chen‐Guang Zheng (Zoologica Scripta, 2022)
Evolutionary analysis of Prodiamesinae has long been impeded by lack of information, and its phylogenetic relationship with Orthocladiinae remains questionable. Here, ten complete mitochondrial genomes (mitogenomes) of Orthocladiinae sensu lato were newly sequenced, including three Prodiamesinae species and seven Orthocladiinae species. Coupled with published mitogenomes, a total of 12 mitogenomes of Orthocladiinae sensu lato were selected for a comparative mitogenomic analysis and phylogenetic reconstruction. Mitogenomes of Orthocladiinae sensu lato are conserved in structure, and all genes arrange the same gene order as the ancestral insect mitogenome. Nucleotide composition is highly biased, and the control region displayed the highest A + T content. All protein‐coding genes are under purifying selection, and the ATP8 evolves at the fastest rate. In addition, the mitogenomes of Orthocladiinae sensu lato are highly conserved, and they are practically useful for phylogenetic inference, suggesting a re‐classification of Orthocladiinae by sinking Prodiamesinae as a subgroup of Orthocladiinae.

GW10, a member of P450 subfamily regulates grain size and grain number in rice - Penglin Zhan; Xin Wei; Zhili Xiao; Xiaoling Wang; Shuaipeng Ma; Shaojun Lin; Fangping Li; Suhong Bu; Zupei Liu; Haitao Zhu; Guifu Liu; Guiquan Zhang; et al. (Theoretical and Applied Genetics, 2021)

Paraburkholderia sp. GD17 improves rice seedling tolerance to salinity - Ruanming Zhu; Yuting Cao; Guangzhe Li; Ying Guo; Lianju Ma; Ning Bu; Lin Hao (Plant and Soil, 2021)

Temperature sensitivity of SOM decomposition is linked with a K‐selected microbial community - Hui Li; Shan Yang; Mikhail V. Semenov; Fei Yao; Ji Ye; Rencang Bu; Ruiao Ma; Junjie Lin; Irina Kurganova; Xugao Wang; Ye Deng; Irina Kravchenko; et al. (Global Change Biology, 2021)
Temperature sensitivity (Q 10 ) of soil organic matter (SOM) decomposition is a crucial parameter to predict the fate of soil carbon (C) under global warming. Nonetheless, the response pattern of Q 10 to continuous warming and the underlying mechanisms are still under debate, especially considering the complex interactions between Q 10 , SOM quality, and soil microorganisms. We examined the Q 10 of SOM decomposition across a mean annual temperature (MAT) gradient from −1.9 to 5.1°C in temperate mixed forest ecosystems in parallel with SOM quality and bioavailability, microbial taxonomic composition, and functional genes responsible for organic carbon decomposition. Within this temperature gradient of 7.0°C, the Q 10 values increased with MAT, but decreased with SOM bioavailability. The Q 10 values increased with the prevalence of K‐strategy of soil microbial community, which was characterized by: (i) high ratios of oligotrophic to copiotrophic taxa, (ii) ectomycorrhizal to saprotrophic fungi, (iii) functional genes responsible for degradation of recalcitrant to that of labile C, and (iv) low average 16S rRNA operon copy number. Because the recalcitrant organic matter was mainly utilized by the K‐strategists, these findings independently support the carbon quality‐temperature theory from the perspective of microbial taxonomic composition and functions. A year‐long incubation experiment was performed to determine the response of labile and recalcitrant C pools to warming based on the two‐pool model. The decomposition of recalcitrant SOM was more sensitive to increased temperature in southern warm regions, which might attribute to the dominance of K‐selected microbial communities. It implies that climate warming would mobilize the larger recalcitrant pools in warm regions, exacerbating the positive feedback between increased MAT and CO 2 efflux. This is the first attempt to link temperature sensitivity of SOM decomposition with microbial eco‐strategies by incorporating the genetic information and disentangling the complex relationship between Q 10 and soil microorganisms.

Enhanced antioxidant capacity and upregulated transporter genes contribute to the UV-B-induced increase in blinin in Conyza blinii - Junyi Zhan; Qin Yang; Zhiyi Lin; Tianrun Zheng; Maojia Wang; Wenjun Sun; Tongliang Bu; Zizhong Tang; Chenglei Li; Xueyi Han; Haixia Zhao; Qi Wu; et al. (Environmental Science and Pollution Research, 2021)

Ferrous iron-induced increases in capitate glandular trichome density and upregulation of CbHO-1 contributes to increases in blinin content in Conyza blinii - Tianrun Zheng; Maojia Wang; Junyi Zhan; Wenjun Sun; Qin Yang; Zhiyi Lin; Tongliang Bu; Zizhong Tang; Chenglei Li; Jun Yan; Zhi Shan; Hui Chen (Planta, 2020)

A shadow detection and removal method for fruit recognition in natural environments - Rongbin Bu; Juntao Xiong; Shumian Chen; Zhenhui Zheng; Wentao Guo; Zhengang Yang; Xiaoyun Lin (Precision Agriculture, 2020)

Antibacterial activity of ruthenium polypyridyl complexes against Staphylococcus aureus and biofilms - Simeng Bu; Guijuan Jiang; Guangbin Jiang; Jinyao Liu; Xiaoli Lin; Jihong Shen; Yanshi Xiong; Xuemin Duan; Jintao Wang; Xiangwen Liao (JBIC Journal of Biological Inorganic Chemistry, 2020)

Aberrant white matter properties of the callosal tracts implicated in girls with attention-deficit/hyperactivity disorder - Qingxia Lin; Xuan Bu; Meihao Wang; Yan Liang; Hong Chen; Weiqian Wang; Yanhong Yi; Haixi Lin; Jiaxiu Zhou; Lu Lu; Xinyu Hu; Chuang Yang; et al. (Brain Imaging and Behavior, 2020)

Model test for water inrush caused by karst caves filled with confined water in tunnels - Weimin Yang; Xin Yang; Zhongdong Fang; Shaoshuai Shi; Hao Wang; Lin Bu; Liping Li; Zongqing Zhou (Arabian Journal of Geosciences, 2019)

Numerical Investigation to Influence of Perforation Angle on Hydraulic Fracturing Process - Lin Bu; Shucai Li; Shaoshuai Shi; Xiaokun Xie; Liping Li; Zongqing Zhou (Geotechnical and Geological Engineering, 2019)

Development of an Improved Immersing Method to Enhance Microbial Induced Calcite Precipitation Treated Sandy Soil through Multiple Treatments in Low Cementation Media Concentration - Kejun Wen; Yang Li; Shihui Liu; Changming Bu; Lin Li (Geotechnical and Geological Engineering, 2019)

Degradation of diethyl phthalate (DEP) by vacuum ultraviolet process: influencing factors, oxidation products, and toxicity assessment - Yangtao Wu; Lin Deng; Lingjun Bu; Shumin Zhu; Zhou Shi; Shiqing Zhou (Environmental Science and Pollution Research, 2019)

Application of the comprehensive forecast system for water-bearing structures in a karst tunnel: a case study - Lin Bu; Shucai Li; Shaoshuai Shi; Lipin Li; Yong Zhao; Zongqing Zhou; Lichao Nie; Huaifeng Sun (Bulletin of Engineering Geology and the Environment, 2019)

Ras-Related C3 Botulinum Toxin Substrate 1 Promotes Axonal Regeneration after Stroke in Mice - Lin Liu; Hui Yuan; Yanhua Yi; Edward C. Koellhoffer; Yashasvee Munshi; Fan Bu; Yi Zhang; Zhenggang Zhang; Louise D. McCullough; Jun Li (Translational Stroke Research, 2018)

A New Advance Classification Method for Surrounding Rock in Tunnels Based on the Set-Pair Analysis and Tunnel Seismic Prediction System - Lin Bu; Shu-cai Li; Shao-shuai Shi; Xiao-kun Xie; Li-ping Li; Zong-qing Zhou; Zhi-jie Wen (Geotechnical and Geological Engineering, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

Plasma Amyloid-Beta Levels in Patients with Different Types of Cancer - Wang-Sheng Jin; Xian-Le Bu; Yu-Hui Liu; Lin-Lin Shen; Zhen-Qian Zhuang; Shu-Sheng Jiao; Chi Zhu; Qing-Hua Wang; Hua-Dong Zhou; Tao Zhang; Yan-Jiang Wang (Neurotoxicity Research, 2017)

Full-length genomic characterization and molecular evolution of canine parvovirus in China - Ling Zhou; Qinghai Tang; Lijun Shi; Miaomiao Kong; Lin Liang; Qianqian Mao; Bin Bu; Lunguang Yao; Kai Zhao; Shangjin Cui; Élcio Leal (Virus Genes, 2016)

Sex Dimorphism Profile of Alzheimer’s Disease-Type Pathologies in an APP/PS1 Mouse Model - Shu-Sheng Jiao; Xian-Le Bu; Yu-Hui Liu; Chi Zhu; Qing-Hua Wang; Lin-Lin Shen; Cheng-Hui Liu; Ye-Ran Wang; Xiu-Qing Yao; Yan-Jiang Wang (Neurotoxicity Research, 2016)

Degradation of oxcarbazepine by UV-activated persulfate oxidation: kinetics, mechanisms, and pathways - Lingjun Bu; Shiqing Zhou; Zhou Shi; Lin Deng; Guangchao Li; Qihang Yi; Naiyun Gao (Environmental Science and Pollution Research, 2016)

Elemental sulfur in northern South China Sea sediments and its significance - Qi Lin; JiaSheng Wang; ShaoYing Fu; HongFeng Lu; QingTao Bu; RongXiao Lin; Fei Sun (Science China Earth Sciences, 2015)

Serum Amyloid-Beta Levels are Increased in Patients with Chronic Obstructive Pulmonary Disease - Xian-Le Bu; Guo-Qiang Cao; Lin-Lin Shen; Yang Xiang; Shu-Sheng Jiao; Yu-Hui Liu; Chi Zhu; Fan Zeng; Qing-Hua Wang; Ye-Ran Wang; Yong He; Hua-Dong Zhou; et al. (Neurotoxicity Research, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Regression Analysis of Non-iatrogenic Factors That Determine Adherence to Radiation Therapy - Xiangzhao Bu; Xuemei Fan; Dawei Hao; Lin Guo; Chengjun Wu; Chong Zhou (Cell Biochemistry and Biophysics, 2015)

Association between the CYP2E1 polymorphisms and lung cancer risk: a meta-analysis - Xiang-Hua Ye; Liang Song; Ling Peng; Zhibin Bu; Sen-Xiang Yan; Jie Feng; Xin-Li Zhu; Xin-Biao Liao; Xue-Lin Yu; Danfang Yan (Molecular Genetics and Genomics, 2015)

Mapping Quantitative Trait Loci for Omega-3 Fatty Acids in Asian Seabass - Jun Hong Xia; Grace Lin; Xiaoping He; Bu Yunping; Peng Liu; Feng Liu; Fei Sun; Rongjian Tu; Gen Hua Yue (Marine Biotechnology, 2014)

Effect of Selenium on the Interaction Between Daunorubicin and Cardiac Myosin - Yang Liu; Bu-hai Li; Xiao-mei Sun; Ai-hua Lin; De-bin Wang (Biological Trace Element Research, 2012)

Alleviative effect of quercetin on germ cells intoxicated by 3-methyl-4-nitrophenol from diesel exhaust particles - Tong-liang Bu; Yu-dong Jia; Jin-xing Lin; Yu-ling Mi; Cai-qiao Zhang (Journal of Zhejiang University-SCIENCE B, 2012)

Association of polymorphisms in folate metabolic genes and prostate cancer risk: a case-control study in a Chinese population - Dawei Cai; Lin Ning; Chunyu Pan; Xuefeng Liu; Renge Bu; Xiaonan Chen; Kefeng Wang; Yang Cheng; Bin Wu (Journal of Genetics, 2010)

Phylogenetic analysis and screening of antimicrobial and cytotoxic activities of moderately halophilic bacteria isolated from the Weihai Solar Saltern (China) - Lei Chen; Guangyu Wang; Tong Bu; Yunbin Zhang; Yixin Wang; Ming Liu; Xiukun Lin (World Journal of Microbiology and Biotechnology, 2010)

Cellular and molecular responses in progressive pseudorheumatoid dysplasia articular cartilage associated with compound heterozygous WISP3 gene mutation - Hou-De Zhou; Yan-Hong Bu; Yi-Qun Peng; Hui Xie; Min Wang; Lin-Qing Yuan; Yi Jiang; Duo Li; Qi-You Wei; Yu-Ling He; Tao Xiao; Jiang-Dong Ni; et al. (Journal of Molecular Medicine, 2007)

Assessment of indirect use values of forest biodiversity in Yaoluoping national nature reserve, Anhui province - Hui Xu; Yi Qian; Lin Zheng; Bu-zhuo Peng (Chinese Geographical Science, 2003)